Place of topical corticosteroids in therapy of allergic rhinitis - S. V. Ryazantsev; S. A. Artuyshkin; M. A. Budkovaya; E. S. Artemyeva (Медицинский совет, 2018)
Treatment of allergic rhinitis (AR) is an important medical and social problem. Priority in choosing the tactics of managing patients with this pathology is the appointment of intranasal corticosteroids in the form of basic AR therapy and as part of combined schemes.